218 Socioeconomic Status in Relation to Lipid and Glucose Metabolism in Early Childhood. The ABCD-Study. (October 2012) - Berg, G van den; Eijsden, M van; Vrijkotte, TGM; Gemke, RJBJ
Abstract : Objective: The objective of this study was to explore the relations of socioeconomic status to lipid and glucose metabolism as indicators of cardiovascular health in 5–6 year olds. Methods: In 1308 5–6 year old ethnic Dutch children from the ABCD cohort study, lipids (cholesterol, LDL-C, HDL-C, triglycerides), glucose and C-peptide (n = 974) were measured after an overnight-fast. Insulin resistance was calculated with HOMA. Using linear regression the association of lipid and glucose metabolism to socioeconomic status as indicated by maternal education and income adequacy was examined. Results: There were no differences in cholesterol, HDL-C, LDL-C, and triglycerides between socioeconomic groups. However, children with low educated mothers had on average a higher glucose (p=0.01), C-peptide (p = 0.001), and insulin resistance (p = 0.001) compared to children with high educated mothers. These associations could not be explained by birth weight, maternal BMI, breastfeeding duration, and physical activity. Childhood BMI partly explains these associations, but after adjustment for BMI the association between maternal education and markers of the glucose metabolism remained significant (models controlled for age, height, and sex). Conclusion: Socioeconomic status appears to be an independent risk factor for cardiovascular function and seems to emerge in early childhood. In absence of underlying mechanisms these empirical findings are relevant for public health care and further explanatory research.